Colicins and Salmocins – New Classes of Plant-Made Non-antibiotic Food Antibacterials - Hahn-Löbmann, Simone; Stephan, Anett; Schulz, Steve; Schneider, Tobias; Shaverskyi, Anton; Tusé, Daniel; Giritch, Anatoli; Gleba, Yuri (Frontiers in Plant Science, 2019)
Recently, several plant-made recombinant proteins received favorable regulatory review as food antibacterials in the USA through the GRAS regulatory procedure, and applications for others are pending. These food antimicrobials, along with approved biopharmaceuticals and vaccines, represent new classes of products manufactured in green plants as production hosts. We present results of new research and development and summarize regulatory, economic and business aspects of the antibacterial proteins colicins and salmocins as new food processing aids.